MASSAGE AND ITS TYPES, PHYSIOLOGICAL EFFECT (Proceedings of International Educators Conference, 2024)
This article offers a comprehensive study of the various types and techniques of massage, including the various methods, techniques, and therapeutic approaches used in the practice of massage therapy. It explores the principles, benefits, and applications of popular massage techniques, including Swedish massage, deep tissue massage, aromatherapy massage, Thai massage, and reflexology, while highlighting new trends and innovative methodologies in massage therapy. The article will serve as a valuable resource for individuals seeking to deepen their understanding of the multifaceted nature of massage and its potential effects on physical, mental, and emotional well-being.